Organizational culture in school administration in girls’ schools, Asir Education, during the Corona pandemic - Hamed, Norah Khaloofah (Journal of Educational and Psychological Sciences, 2024)
The aim of this field study was to identify the level of organizational culture in school management at girls' schools in Asir Education during the COVID-19 pandemic and to examine the impact of study variables on their perspectives. The researcher used the descriptive survey method, and the tool was a questionnaire distributed to a sample of 45 female principals. The results showed that the degree of organizational culture practice by school principals in Asir Education was at an average of 3.30 out of 5, with a "moderate" level. Regarding the organizational dimensions, the values were as follows: the highest average was for organizational values (3.48), rated as "large," followed by beliefs (3.39), norms (3.19), and expectations (3.15), all rated as "moderate." Statistically significant differences were found at the (α≤0.05) level, attributed to educational qualifications, in favor of a doctorate, years of service, in favor of 5-10 years, school location, in favor of schools located more than 50 km away, and student density, in favor of schools with 401 or more students. Based on the results, the researcher recommended developing organizational culture in light of modern trends in school management, preparing specialized training programs for school principals to enhance their organizational culture, and including organizational culture dimensions as criteria for selecting school principals.
Keywords: organizational culture; school administration; Corona pandemic